Implementation of voyage data recording device using a digital forensics-based hash algorithm - Ki-Taek Seong; Gwan-Hyung Kim (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Identifying the causes of marine accidents is difficult because of problems in scene preservation, reenactment, and procuring of witnesses. Thanks to new regulations, larger vessels are now required to carry voyage data recorders (VDRs) and automatic identification systems (AISs). However, the content of these devices, which is created, stored, and managed digitally, has security vulnerabilities such as the potential for data modification. Therefore, when managing digital records it is important to guarantee reliability. To this end, we suggest a digital forensics-based digital records migration method using a hash algorithm to guarantee the integrity and authenticity of digital records.